Transcranial Imaging of Functional Cerebral Hemodynamic Changes in Single Blood Vessels using in vivo Photoacoustic Microscopy - Liao, Lun-De; Lin, Chin-Teng; Shih, Yen-Yu I; Duong, Timothy Q; Lai, Hsin-Yi; Wang, Po-Hsun; Wu, Robby; Tsang, Siny; Chang, Jyh-Yeong; Li, Meng-Lin; Chen, You-Yin (Journal of cerebral blood flow and metabolism, 2012)
Optical imaging of changes in total hemoglobin concentration (HbT), cerebral blood volume (CBV), and hemoglobin oxygen saturation (SO2) provides a means to investigate brain hemodynamic regulation. However, high-resolution transcranial imaging remains challenging. In this study, we applied a novel functional photoacoustic microscopy technique to probe the responses of single cortical vessels to left forepaw electrical stimulation in mice with intact skulls. Functional changes in HbT, CBV, and SO2 in the superior sagittal sinus and different-sized arterioles from the anterior cerebral artery system were bilaterally imaged with unambiguous 36 × 65-μm2 spatial resolution. In addition, an early decrease of SO2 in single blood vessels during activation (i.e., ‘the initial dip’) was observed. Our results indicate that the initial dip occurred specifically in small arterioles of activated regions but not in large veins. This technique complements other existing imaging approaches for the investigation of the hemodynamic responses in single cerebral blood vessels.